Pelatihan Menyusun Menu Seimbang dengan Pemanfaatan Pangan Lokal untuk Tumbuh Kembang Balita Sehat dalam Pencegahan Wasting Secara Dini - Rotua, Manuntun; Sihite, Natasha Weisdania (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: Malnutrition, particularly among pregnant women and toddlers, remains a significant issue in Indonesia. One approach to reducing wasting rates involves direct counseling and empowering mothers of toddlers with the skills to prepare balanced menus using local food for their families, especially for toddlers suffering from wasting. Enhance mothers’ knowledge in preparing balanced menus for toddlers, increasing the benefits of the menu for the growth and development of toddlers. This training activity was carried out over 4 meetings, at the PKM Sukarami Hall, via an online WA group, a menu competition was held at the PKM Sukarami Hall and at the Posyandu, and evaluation monitoring through weighing at the Posyandu. There were 30 participants consisting of 10 posyandu cadres and 20 mothers of toddlers from the Sukarami Health Center working area, Palembang city. Method used in the training is first a pre-test, lecture, question and answer discussion, and post-test, practical demonstration of menu processing and menu competition. Monitoring and evaluation looks at the growth and development of toddlers through weighing. The success of organizing this community service can be seen from the enthusiasm of the group of participants who attended.  Results :  the mothers' knowledge met the initial score criteria of 37% to 60% with an increase of 23%, skills in providing a healthy, balanced nutritional menu. Conclusion: there were 20 toddlers showed weight increases ranging from 100 grams to 260 grams.